Enhanced activity of vancomycin by encapsulation in hybrid magnetic nanoparticles conjugated to a cell-penetrating peptide. Issue 6 (30th January 2020) - Zhang, Wenjie; Taheri-Ledari, Reza; Hajizadeh, Zoleikha; Zolfaghari, Ehsan; Ahghari, Mohammad Reza; Maleki, Ali; Hamblin, Michael R.; Tian, Ye
Abstract : We describe a novel antibiotic delivery system based on magnetic nanoparticles (NPs) conjugated to a cell-penetrating peptide (CPP). Abstract : We describe a novel antibiotic delivery system based on magnetic nanoparticles (NPs) conjugated to a cell-penetrating peptide (CPP). Silica-coated iron oxide NPs were produced via a co-deposition method, and coated by a polyvinyl alcohol (PVA) polymeric network via physicochemical binding. Vancomycin (VAN) was then entrapped into this PVA network. A hexapeptide sequence Gly-Ala-Phe-Pro-His-Arg, was synthesized in the solid phase and then conjugated onto the surface of the magnetic NPs. The drug ratio incorporation into the carrier system and drug release were monitored through precise analysis. Confocal microscopy showed that the NPs could be internalized into Staphylococcus aureus and Escherichia coli bacterial cells. The antimicrobial effects of VAN were significantly enhanced by this system with a low dosage of VAN. Advantages include rapid targeted-drug delivery process, drug dose reduction, and equal effects on both Gram-positive and Gram-negative bacteria.